Effects of coaches’ autonomy support on athletes’ aggressive behavior and athlete burnout: verification of the mediating effects of coach-athlete relationship and team efficacy - Kim, Suk-Kyu; Choi, Hunhyuk (Frontiers in Psychology, 2024)
Purpose This study investigated the relationships between perceived autonomy support, coach–athlete relationship, team efficacy, aggressive behavior, and athlete burnout among team sports athletes. It verified the mediating effects of the coach–athlete relationship and team efficacy on the relationship between autonomy support and athlete burnout. Design, methodology, and approach A questionnaire survey on autonomy support, coach–athlete relationships, aggressive behavior, and athlete burnout was administered to 336 team sports athletes (292 male athletes and 44 female athletes). A cross-sectional research design was used to collect the data. To analyze the collected data, frequency, reliability, descriptive statistical, and correlation analyses were performed using SPSS version 26.0. In addition, confirmatory factor analysis, convergent validity tests, and structural model analysis were conducted using AMOS version 24.0. Bootstrapping was used to examine the mediating effects. Results The fit of the measurement model was assessed by calculating the fit indices as follows: x2 = 329.689, df = 124, p < 0.001, TLI = 0.945, CFI = 0.956, RMSEA = 0.070 (90% CI = 0.061–0.080), and SRMR = 0.060. Autonomy support positively affected the coach–athlete relationship (β = 0.841) and team efficacy (β = 0.338). The coach–athlete relationship positively affected team efficacy (β = 0.479). Furthermore, autonomy support did not significantly influence aggressive behavior (β = −0.053), and negatively affected athlete burnout (β = −0.305). The coach–athlete relationship also did not significantly affect aggressive behavior (β = 0.054), and negatively affected athlete burnout (β = −0.303). Team efficacy negatively affected aggressive behavior (β = −0.516) and athlete burnout (β = −0.201). Finally, autonomy support was found to affect athlete burnout through the coach–athlete relationship and team efficacy. Conclusion Considering that autonomy support affects athlete burnout through coach–athlete relationship and team efficacy, coaches need to enhance the quality of the coach–athlete relationship and improve team efficacy to reduce athlete burnout. Above all, the study findings suggest that coaches need to provide autonomy-supportive behaviors.